Nonlinear fractional equations with supercritical growth - Li, Lin; Agarwal, Ravi P. P.; Li, Chun (Nonlinear Analysis: Modelling and Control, 2017)
We obtain existence of infinitely many solutions for a fractional differential equation with indefinite concave nonlinearities and supercritical growth.